Efficacy of 308 nm Excimer laser in the treatment of vitiligo: A Retrospective study - Rajegowda, Harish Muddanahalli; Madegowda, Shashi Kumar Basavapura; Kalegowda, Deepadarshan; Thabassum A, Dr. (Journal of Pakistan Association of Dermatologists, 2019)
Background Vitiligo is a chronic, polygenic dyschromia that presents with multiple depigmented macules & patches. Widespread prejudices, ignorance, taboos, lack of scientific appraisal and confusion of vitiligo with leprosy all makes it an immense psychological stress. Objectives To determine the efficacy of 308 nm excimer laser in vitiligo. Materials and Methods Record based retrospective study of 40 patients with localized vitiligo who were treated with 308nm excimer laser were included. Twice weekly 308nm excimer laser (Eximal elite, GSD®) was given to 40 patients with 120 vitiligo lesions till complete resolution or till maximum 30 sessions whichever occurred earlier. Initial doses used were of 200-250mJ/cm2 with increments of 50mJ/cm2 every session. Repigmentation was monitored by serial photographs and graded as excellent (≥75% repigmentation), good (50−74% repigmentation) and poor (<50% repigmentation) at the end of study period. The extent of repigmentation achieved was correlated with site of the lesion. Results A total of 40 patients each with 1-5 vitiligo lesions between age group of 6-69 years were included. Females outnumbered males in the ratio of 1.5:1. Majority of the patients belonged to <15 years age group. Seven patients had segmental vitiligo while 33 were diagnosed as non segmental vitiligo. The most common site affected was lower limbs followed by trunk. Out of 120 lesions treated, 32 lesions (26.6%) showed excellent response. Among rest of 88 lesions, 39 lesions (32.5%) failed to show satisfactory response to treatment while 40.8% showed good response. Lesions on trunk responded best to treatment followed by lower limb. Eighteen (45%) patients aged less than 18 years showed excellent to good response. Conclusion 308nm excimer laser is as promising therapy in treatment of localized vitiligo especially in children with rapid onset of repigmentation as early as 3 sessions of treatment. Limitations The study is limited by its retrospective nature and small sample size.